Analysing the thermal state of voltage transformer based on resistive voltage divider. Issue 1 (September 2015) - Lebedev, V; Zhukov, V; Yablokov, A
Abstract: We performed a simulation of the thermal state of a resistive voltage divider based on an equation of heat conductivity with internal sources of heat, solving this equation by using two numerical procedures. We also conducted experimental research regarding transformer thermal state on a laboratory stand. We obtained numerical results of the above heat conductivity equation, taking into account the supply of heat energy from internal sources, and compared the results of our calculations with our experimental data. Transformer thermal state simulation and numerical solution procedures enable us to formulate and resolve the problems of choosing optimal transformer design and operating modes, ensuring maximum measuring accuracy when limiting the thermal state of resistive elements.